The expression of Bcl-2 anti- apoptotic protein in colorectal adenocarcinoma - Danijela Batinić Škipina; Slavica Knežević Ušaj; Dragana Zec; Mirjana Ćuk; Snežana Božanić; Nenad Lalović (Биомедицинска истраживања, 2010)
Introduction: The Bcl-2 gene codes an oncoprotein, inhibits a programmed cell death or apoptosis and it plays a very important role in colorectal cancerogenesis. The aim of our study is to determine Bcl-2 expression in colorectal carcinomas in relation with the stage of disease, histology of tumor type, localization and macroscopic growth pattern. Methods: Immunohistochemichal detection of Bcl-2 protein expression was carried out on 90 resected colorectal carcinomas. The patients were divided into three groups according to the degree of Bcl-2 expression in a tumor: group 0 - there were no cells with positive immunohistochemical reaction; group I- up to 20 % of positive cells, and group II- above 20% of positive cells. The groups were compared in relation to the stage of disease, T stage of local spread of disease, histology of tumor type, localization and macroscopic growth pattern. Results: 58% of patients at the second stage of disease had no expression of Bcl-2. Higher percentage (61%) of the patients with metastases ( stages III and IV) had high level of Bcl-2 expression. Tumors with polipoid growth pattern have higher level of Bcl-2 expression. Conclusion: There is a statisticaly significant difference in Bcl-2 protein expression in patients surgically treated at the II and III stage of disease, stage T3a/b, T3c/d of local spread of disease and tumors whith polipoid growth pattern in relation to infiltrative growth pattern.
Keywords: colorectal carcinoma; apoptosis; Bcl-2; stage of disease